KONTRIBUSI KURIKULUM PESANTREN DALAM MENINGKATKAN KEMAMPUAN MEMBACA DAN MENULIS AL-QUR’AN - Muthmainnah Muthmainnah (QATHRUNÂ, 2019)
The purpose of this study is to describe and analyze the contribution of the pesantren curriculum in improving the quality of students' reading and writing skills at the Mardhatillah al-Mumtazah and Daar el-Ulum Saketi Pandeglang Islamic Boarding School. This research is a type of qualitative descriptive research, and through educational and sociological approaches. The research location was conducted in two Islamic boarding schools, namely Mardhatillah al-Mumtazah and Daar el-Ulum, Saketi district. Results and discussion, namely the curriculum design of the Mardhatillah al-Mumtazah Islamic Boarding School in improving the ability to read al-Qurán is by applying the Tahsin model and adjusting it to the objectives expected by the boarding school to improve reading and writing skills. Meanwhile, the pesantren curriculum model in improving writing skills is the Imla 'model with the imla method of copying and listening to readings. The Daar el-Ulum pesantren curriculum model in improving reading skills is the Tahsin model. Meanwhile, the Daar el-Ulum Islamic boarding school curriculum model in improving writing skills is the Imla 'model, with the imla writing method moving, copying and listening to readings or sentences from a media. In this case there is a slight difference in the method and subject matter. As for the implementation of the pesantren curriculum in improving the ability to read and write al-Qurán at the Mardhatillah al-Mumtazah Islamic Boarding School, namely privately or individually, classically and in groups. By using predetermined teaching methods and predetermined material and evaluation. Whereas in the Daar el-Ulum Islamic Boarding School the implementation is the same as the Mardhatillah al-Mumtzah Islamic boarding school individually or privately, classical or in groups, with the teaching method that has been adjusted.